2014
DOI: 10.3389/fnbeh.2014.00375
|View full text |Cite
|
Sign up to set email alerts
|

Nocebo Effect in Randomized Clinical Trials of Antidepressants in Children and Adolescents: Systematic Review and Meta-Analysis

Abstract: Objective: To compare the incidence of adverse events between active and placebo arms of randomized clinical trials in depressive children and adolescents (C&A) with antidepressant treatments, in order to look for similarities in both groups that allow to establish a possible nocebo effect.Methods: Systematic search strategy (January 1974–March 2013) in electronic databases, conference abstracts, and reference list of systematic reviews and included studies to identify parallel randomized placebo-controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 56 publications
0
24
0
6
Order By: Relevance
“…The small amount of research on SNRIs for pediatric DD has had mixed results 3 . One meta-analysis on pediatric depression found that while SSRIs differed significantly from placebo, SNRIs and tricyclic antidepressants did not 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small amount of research on SNRIs for pediatric DD has had mixed results 3 . One meta-analysis on pediatric depression found that while SSRIs differed significantly from placebo, SNRIs and tricyclic antidepressants did not 6 .…”
Section: Introductionmentioning
confidence: 99%
“…For adult patients with DD, a genuine placebo effect has been demonstrated, as the combination of placebo and supportive care has been shown to be more effective than supportive care alone 13 . Conversely, patients in the placebo group also demonstrate treatment emergent adverse events 6 . However, how response to placebo differs across disorders or other study design features in pediatrics remains understudied.…”
Section: Introductionmentioning
confidence: 99%
“…True placebo response would be symptom improvements in the non‐active treatment arm that go above and beyond spontaneous remission in the no‐treatment group. Likewise, true nocebo responses are adverse effects that go above and beyond symptoms in the no‐treatment group’ . While a similar degree of adverse effects in a treatment and placebo group can give reassurance that adverse effects are not drug‐related, it cannot estimate the extent to which expectation of an adverse effect is responsible for the patient experiencing the effect.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally altering patients’ beliefs about whether they are taking an active medication has sometimes been found to enhance the effects of placebos (Vase et al, 2002). Similarly, side effect profiles in the placebo arms of clinical trials often resemble those of the active drug comparator (Mora et al, 2011; Rojas-Mirquez et al, 2014) (i.e., a nocebo effect), and manipulating patients’ side effect expectations affects their reports of side effects (Mondaini et al, 2007; Wise et al, 2009). …”
Section: Introductionmentioning
confidence: 99%